Synthesis of nanostructured SnO2 for lithium‐ion batteries. - Ng, Mei Feng. (2012)
This report presents the development of a novel hydrothermal synthesis method to prepare tin dioxide (SnO2) with a unique nanostructure for lithium-ion battery (LIB) application. This project requires the use of scanning electron microscope (SEM) and transmission electron microscope (TEM) to study the structure of the sample. X-ray diffraction (XRD) is employed to determine the purity of SnO2 obtained.